PENGARUH MODEL PEMBELAJARAN MULTIPLE INTELLIGENCES TERHADAP CIVIC KNOWLEDGE DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKN DI SMP NEGERI 3 TAROGONG KIDUL - Alaya, Indika; Jamilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of the Multiple Intelligences learning model on Civic Knowledge and student learning outcomes in the Civics (PPKn) subject at SMP Negeri 3 Tarogong Kidul. The research utilized a quasi-experimental method with a non-equivalent control group design, involving homogeneous samples divided into experimental and control groups. The results indicate that, statistically, there is no significant difference between the experimental class which implemented the Multiple Intelligences model and the control class which utilized conventional methods regarding both Civic Knowledge and cumulative learning outcomes. However, deeper analysis reveals that students' initial academic ability acts as a dominant moderating variable; this model proved to have a positive and accelerative influence on students with high academic ability, yet it was less effective for students with low academic ability without intensive guidance. Therefore, the implementation of the Multiple Intelligences model in Civics education requires proportional process differentiation to accommodate the diversity of student capacities, ensuring optimal learning outcomes for all students.